ETNOBOTANI TUMBUHAN OBAT YANG DIGUNAKAN SUKU ANAK DALAM DI DESA TABUN KECAMATAN VII KOTO KABUPATEN TEBO JAMBI - Indriati, Gustina (Sainstek : Jurnal Sains dan Teknologi, 2014)
This research investigated traditional medicine used by primitive tribes in order to cure their diseases. This study was conducted in December 2010 at small town, Taban, VII Koto district. The method used in this research was descriptive survey. The result of this research showed that there were 39 kinds of medical plants derived from 33 families. The plants scientifically could cure 27 kinds of diseases.Key words: traditional medicine, primitive tribes